2015
DOI: 10.1002/bbb.1613
|View full text |Cite
|
Sign up to set email alerts
|

The feasibility of short‐term production strategies for renewable jet fuels – a comprehensive techno‐economic comparison

Abstract: This study compares the short-term economic feasibility of six conversion pathways for renewable jet fuel (RJF) production. The assessment combines (i) a harmonized techno-economic analysis of conversion pathways expected to be certifi ed for use in commercial aviation by 2020, (ii) a pioneer plant analysis taking into account technological immaturity, and (iii) a quantifi ed assessment of the merits of co-producing RJF alongside existing European supply chains in the pulp, wheat ethanol, and beet sugar indust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
218
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 229 publications
(257 citation statements)
references
References 62 publications
6
218
1
Order By: Relevance
“…A sensitivity analysis on bio‐based plants' CAPEX was also conducted. Economic analysis tends to underestimate the capital costs and overestimate the plant performance if compared with values observed for a first‐of‐a‐kind (pioneer) plant . An uncertainty range of −50% to 100% was therefore applied to the CAPEX of both bio‐based ethylene processes.…”
Section: Methodsmentioning
confidence: 99%
“…A sensitivity analysis on bio‐based plants' CAPEX was also conducted. Economic analysis tends to underestimate the capital costs and overestimate the plant performance if compared with values observed for a first‐of‐a‐kind (pioneer) plant . An uncertainty range of −50% to 100% was therefore applied to the CAPEX of both bio‐based ethylene processes.…”
Section: Methodsmentioning
confidence: 99%
“…The drop-in quota is based on several types of alternative fuels that have been certified according to ASTM D7566 (standard specification for aviation turbine fuels) [8]. The time to adjust production capacity for alternative jet fuels is derived from a production start-up schedule for renewable jet fuels given in de Jong et al and varied in order to take into account uncertainties [38]. Similarly, uncertainties related to the development of conventional jet fuel prices are taken into account by varying prices to grow at different growth rates of their past average.…”
Section: Data Base and Simulation Set Upmentioning
confidence: 99%
“…The authors found that feedstock cost contributes the most to breakeven price, and that the breakeven price of middle distillate HEFA from YG and tallow was higher than petroleum-derived diesel fuel prices, but lower than the breakeven price of soybean oil HEFA. de Jong et al [28] compared six short-term renewable jet fuel pathways by combining possible feedstocks and technologies, as well as ten greenfield, three retro-fitting, and nine co-locating strategies. Their results showed that HEFA is the most competitive pathway in the short term.…”
Section: Introductionmentioning
confidence: 99%